KEPUASAN PETANI PLASMA KELAPA SAWIT TERHADAP IMPLEMENTASI KEMITRAAN INTI PLASMA - Pratiwi Sihombing, Windia Deby; Irawan, Andi; Purwoko, Agus (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
The objective of this research analyzed the level of plasma farmers satisfaction on the service performance of Nucleus-Plasma’s partnership implementation by PT. Agricinal. The research was conducted in Putri Hijau District of North Bengkulu Regency. Research site is selected purposively. Data were collected at the study site from March to April 2018. Primary data obtained directly through the questionnaire which is given to oil palm farmers and secondary data were obtained from PT. Agricinal. The sampling method used in this study was Simple Random Sampling and 95 farmers selected randomly as samples. Consumer Satisfaction Index was 74.20% which revealed that smallholders are satisfied with the implementation of the Nucleus-Plasma partnership. The service attributes to be maintained are quick response service, implementation and guarantee the development of KPEN-RP (Credit for Bio-Energy Development and Plantation Revitalization), provide trained counselor, ensure farmers selling price, technical and non technical guidance, the commitment to buy output (fresh fruit bunches) during the partnership contract, making the layout plan in accordance with the company's estate, ensuring farmers got subsidy of interest of KPEN-RP’s credit. The company also must increase the attributes of partnership services namely; 1) the main priority is providing monitoring book on the implementation of partnership to the farmers as a form of transparency in the implementation of partnership contract, and 2) the less important priorities are cattle ownership, development and maintenance of the palm oil farming in accordance with technical standards, cooperatives management was representing farmers in submitting complaints to PT Agricinal, and helped farmers to find sources of another financing.